Targeting Endosomal Recycling Pathways by Bacterial and Viral Pathogens - Yong, Xin; Mao, Lejiao; Shen, Xiaofei; Zhang, Zhen; Billadeau, Daniel D.; Jia, Da (Frontiers in Cell and Developmental Biology, 2021)
Endosomes are essential cellular stations where endocytic and secretory trafficking routes converge. Proteins transiting at endosomes can be degraded via lysosome, or recycled to the plasma membrane, trans-Golgi network (TGN) or other cellular destinations. Pathways regulating endosomal recycling are tightly regulated in order to preserve organelle identity, to maintain lipid homeostasis, and to support other essential cellular functions. Recent studies have revealed that both pathogenic bacteria and viruses subvert host endosomal recycling pathways for their survival and replication. Several host factors that are frequently targeted by pathogens are being identified, including retromer, TBC1D5, SNX-BARs, and the WASH complex. In this review, we will focus on the recent advances in understanding how intracellular bacteria, human papillomavirus (HPV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) hijack host endosomal recycling pathways. This exciting work not only reveals distinct mechanisms employed by pathogens to manipulate host signaling pathways, but also deepens our understanding of the molecular intricacies regulating endosomal receptor trafficking.